Disharmoni Putusan Pengadilan Hubungan Industrial dan Mahkamah Agung dalam Perselisihan Hak Pasca Undang-Undang Cipta Kerja - Angel Evelin Saragih Sitio; Iwan Erar Joesoef; Atik Winanti (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The disharmony of judicial decisions between the Industrial Relations Court and the Supreme Court in resolving rights disputes following the enactment of the Job Creation Law reflects inconsistencies in legal application, which may lead to legal uncertainty for workers. This study aims to analyze the factors causing such disharmony and to examine its implications for the principle of legal certainty in the settlement of industrial relations disputes. This research employs a normative legal method using statutory and case approaches, focusing on a comparative analysis of decisions issued by the Industrial Relations Court and the Supreme Court in rights dispute cases. The findings indicate that the disharmony of decisions is primarily caused by differences in judicial interpretation of legal norms after the Job Creation Law, inconsistencies in the application of legal principles, and the absence of standardized interpretative guidelines. These conditions weaken legal certainty and potentially disadvantage workers as the more vulnerable party in industrial relations. This study proposes a harmonization framework through strengthening legal interpretation guidelines and ensuring consistency in applying the principle of legal certainty as a means to achieve uniformity in resolving rights disputes. Therefore, this research is expected to contribute both theoretically and practically to the development of labor law in Indonesia.